Implementasi Kebijakan Prioritas Penggunaan Dana Desa Untuk Pencapaian SDGs Desa Di Desa Pende Kecamatan Kersana Kabupaten Brebes Tahun 2021 - Maulana, Irhas (JURNAL LANSKAP POLITIK, 2022)
This study aims to describe the Analysis of Priority Policy Implementation for the Use of Village Funds for the Achievement of Village SDGs as an effort to develop and empower rural communities in Pende Village in 2021 and identify supporting and inhibiting factors. This study uses qualitative research methods with qualitative descriptive analysis techniques. The results of the study indicate that the Implementation of the Priority Policy for the Use of Village Funds in 2021 in the village of Pende has carried out conformity with the SOP and the rules of technical guidance in the legislation. However, the process is still not optimal. This can be seen from the lack of information to the public at large or prioritizing people who are close to the village government, the existence of miscommunication between relevant stakeholders and for accountability to the community the lack of transparency. The inhibiting factor that affects the implementation of the priority policy on the use of village funds for the achievement of the village SDGs in 2021 is the occurrence of miscommunication between work units. The supporting factors that influence the implementation of the priority policy on the use of village funds for the achievement of the village SDGs in 2021 are the commitment of the Pende village government in implementing policies, flexible SOPs according to village needs and the enthusiasm of the Pende village community.